2015
DOI: 10.1590/s0102-30982015000000017
|View full text |Cite
|
Sign up to set email alerts
|

Epidemia de sarampo e trabalho escravo no Grão-Pará (1748-1778)

Abstract: O artigo apresenta o impacto populacional provocado pela epidemia de sarampo (1748-1750) na capitania do Grão-Pará e sua relação com o processo de inserção da mão de obra escrava africana. A análise é fundamentada na documentação produzida no século XVIII, levantada em diferentes arquivos brasileiros e portugueses, incluindo correspondências oficiais, crônicas, memórias, mapas populacionais e listagens de mortos pela epidemia. A documentação serial foi posta em base de dados, construída a partir das 80 listage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 3 publications
0
1
0
1
Order By: Relevance
“…The data in table 1 show the climatic variations, along the territorial extension of Brazil. There is a predominance of heat in the northeastern states ( closer to the equator) [12][13][14][15][16][17][18][19], and the report of exposure to heat and cold in the southeast region [2,20]. The exposure to the storms was usual, with the slaves especially susceptible to the more abrupt weather variations.…”
Section: Resultsmentioning
confidence: 99%
“…The data in table 1 show the climatic variations, along the territorial extension of Brazil. There is a predominance of heat in the northeastern states ( closer to the equator) [12][13][14][15][16][17][18][19], and the report of exposure to heat and cold in the southeast region [2,20]. The exposure to the storms was usual, with the slaves especially susceptible to the more abrupt weather variations.…”
Section: Resultsmentioning
confidence: 99%
“…It is necessary to consider the climatic differences among the Brazilian regions to assess clothing and accommodation conditions. The predominance of exposure is to heat in the northeastern states (closest to the Equator) (Assunção 2015;Gayozo 1818;Magalhães 1858;Marques 1870;Prazeres 1891;Schwartz 1988;Vieira Junior and Martins 2015;Viveiros 1954) and to mixed heat and cold in the southeast region (do Alferes and Werneck 1878;Eugenio 2015). However, it was found that the supply of clothing in all regions was reduced.…”
Section: Nineteenth Centurymentioning
confidence: 99%
“…It is necessary to consider the climatic differences between the various regions of Brazil to assess the adequacy of clothing and accommodation conditions. In the northeastern states (closer to the equator), heat exposure is predominant (Assunção 2015;Gayozo 1818;Magalhães 1858;Marques 1870;Prazeres 1891;Schwartz 1988;Vieira Junior and Martins 2015;Viveiros 1954), and in the southeastern region, there is mixed exposure to heat and cold (do Alferes and Werneck 1878; Eugenio 2015). However, there was a reduced supply of clothing in all regions.…”
Section: Twenty-first Centurymentioning
confidence: 99%
“…83 Além das variadas formas de incorporação dos indígenas na sociedade e economia regionais, as transformações que as práticas coloniais provocaram na demografia e nas estruturas sociais de diversos grupos indígenas, suscitam o interesse de pesquisadores. Fora as consequências desastrosas das epidemias que atingiram quase todos os grupos e povos originários, 84 a formação de novas hierarquias e a articulação de políticas indígenas, mediante adaptação e/ou negociação das lideranças tradicionais, estão sendo apontadas em trabalhos recentes. 85 Outros impactos analisados são os complexos processos de mestiçagens, desde os primórdios da colonização, 86 e a ampla difusão da Língua Geral do tronco linguístico tupi.…”
Section: Sujeitos Interagentesunclassified